Development and pilot testing of the treatment and education approach for childhood-onset lupus (TEACH): a cognitive behavioral treatment - Natoshia R. Cunningham (Pediatric Rheumatology Online Journal, 2019)
Abstract Background To develop and test the feasibility and initial effectiveness of the Treatment and Education Approach for Childhood-onset Lupus (TEACH) protocol, a 6-session cognitive behavioral therapy (CBT) intervention for adolescents and young adults (AYA) with childhood-onset systemic lupus erythematosus (cSLE). Methods Females with cSLE (n = 14; ages 13–19 years, M = 16.21 years) presenting to a pediatric rheumatology clinic subsequently completed the protocol, which was iteratively modified based on participant/interventionist feedback. Upon intervention completion, participants provided qualitative data on feasibility, acceptability, potential modifications, and perceived effectiveness of the program via a semi-structured interview, which was analyzed for shared themes. Participants also completed measures of fatigue, psychological distress, and pain intensity before and after the intervention. Nonparametric statistics were conducted to examine changes in outcome measures following the intervention. Results During the study, several protocol modifications were employed to better address the unique needs of individuals with cSLE (e.g., separate content for adolescents versus young adults). Results suggest that TEACH is feasible, acceptable, and potentially effective in the management of cSLE symptoms. Following the intervention, there was a statistically significant reduction in fatigue (Z = − 2.81, p < .01) and depressive symptoms (Z = − 2.69, p < .01). Reductions in pain and anxiety symptoms were marginal. Conclusions TEACH, a tailored CBT protocol for AYA with cSLE, is a feasible and potentially effective intervention for the management of fatigue and depressive symptoms. Future directions include testing the protocol in a larger controlled study.